Robot-oriented design design and management tools for the deployment of automation and robotics in construction - Bock, Thomas 1957-; Linner, Thomas 1979- (Cambridge University Press, 2015)
Robot-Oriented Design introduces the design, innovation, and management methodologies that are key to the realization and implementation of the advanced concepts and technologies presented in the subsequent volumes of the Cambridge Handbooks on Construction Robotics series. This book describes the efficient deployment of advanced construction and building technology. It is concerned with the co-adaptation of construction products, processes, organization, and management, and with automated/robotic technology, so that the implementation of modern technology becomes easier and more efficient. It is also concerned with technology and innovation management methodologies and the generation of life cycle-oriented views related to the use of advanced technologies in construction